Imagining karma: ethical transformation in Amerindian, Buddhist, and Greek rebirth - Obeyesekere, Gananath (Comparative studies in religion and society, 2002)
With 'Imagining Karma', Gananath Obeyesekere embarks on the comparison of rebirth concepts across a wide range of cultures. The book makes a case for disciplined comparison, a humane view of human nature, and a theoretical understanding of 'family resemblances' and differences across great cultural divides